Genomic characterisation of three GES-producing Enterobacterales isolated in the Czech Republic. (June 2022) - Finianos, Marc; Kraftova, Lucie; Papagiannitsis, Costas C.; Adamkova, Vaclava; Hrabak, Jaroslav; Bitar, Ibrahim
Highlights: We report three Entorbacterales isolates harbouring bla GES genes. The is the first report of the new assigned bla OXA-1011 which is suspected to be associated with carbapenems resistance. We report the identification of a novel plasmid sequence carrying the bla GES-7 isolated from a clinical Klebsiella oxytoca isolate. We identifies a hidden source in the hospital environment having Entorbacterales isolates harbouring bla GES genes. There is an increasing trend in Entorbacterales isolates harbouring bla GES genes to duplicate bla GES genes. ABSTRACT: Objectives: The aim of the study is to characterise the genomic features of three GES-producing Enterobacterales isolates from Czech hospitals. Methods: In 2020, during a routine screening of the hospital's surfaces in Prague General Hospital, two strains (CZ862 and CZ863) that belonged to the Enterobacter cloacae complex were found to be bla GES positive. Another bla GES positive strain identified as Klebsiella oxytoca was recovered from a patient hospitalised in Pilsen. Antibiotic susceptibility profiling was done with broth microdilution assay. Conjugation/transformation experiments were performed on all three strains. Genomic DNA of the three isolates was subjected to whole genome sequencing using PacBio platform. Results: Multilocus sequence types typing of CZ862 and CZ863 identified the strains as ST837 and a novel ST (ST1622). Both bla GES harbouring plasmids showed high sequence similarity and complete query coverage (100% and 99.98%) with pEcl-35771cz. Both plasmids had two copies of bla GES instead of one copy as found in pEcl-35771cz. The clinical isolate CZ598 belonged to ST180. The plasmid harboured bla GES-7 gene, cat and aac(6')-lb and the novel variant bla OXA-1011. No similar sequences were observed, suggesting a novel plasmid. Conclusion: The detection of the two bla GES -positive plasmids in the same hospital environment, the first report after 3 years, suggests a hidden source. This highlights the importance of the hidden sources and evolution of such plasmids on the route of spreading into clinical settings. Also, the detection of the new bla OXA-1011, which is thought in this case to be associated with carbapenem resistance, imposes a health risk if disseminated, limiting therapeutic options.